População bacteriana no sêmen suíno e seus efeitos sobre a qualidade da dose inseminante - Chaves, Bruna Resende (2015)
This study was conducted with the objective of verifying the influence of bacteriospermia over the quality of porcine semen, fresh or stored at 15 oC for 72 hours. To do this, 26 ejaculates originated from 26 reproducers were used. Subsequently, the ejaculates were diluted in BTS with no antibiotics in order to obtain inseminating doses containing three billion spermatozoids per inseminating dose. Spermatic quality evaluations were conducted after dilution and after 72 hours of storage, in addition to seminal microbiological evaluation. Each identified microorganism was correlated with the semen quality parameters by means of the Spearman correlation test. In the in natura semen, we identified from one to six typed of bacteria, being Staphylococcus spp. (77% of the samples) and Proteus mirabilis (77%) the most frequent, followed by Burkholderia capacia (35%) and Morganella morganii (31%). In the semen stored for 72 hours, we identified from one to five types of bacteria, being Proteus mirabilis (96% of the samples) the most frequent, folloed by Morganella morganii (31%) and Staphylococcus spp. (27%). The values for total CFU/mL obtained from the stored semen were numerically superior to those obtained from the in natura semen. In the fresh diluted semen, the Pseudomonas putida showed negative correlation with mobility, and positive correlation with sperm viability, while Burkholderia cepacia presented positive correlation with spermatic cell motility and acrosome integrity, and negative correlation in relation to the content of malonic dialdehyde in the semen. In the stored semen, Proteus mirabilis showed negative correlations with spermatic motility and positive correlations with total morphological changes, sperm viability and percentage of whole acrosomes. Pseudomonas putida and Comamonas testosterone presented negative correlations with spermatic motility. Escherichia coli presented negative correlations with sperm viability and percentage of whole acrosomes, while Acinetobacter baumannii calcoaceticus presented positive correlation with the content of malonic dialdehyde and glucose consumption by the spermatozoa. Morganella morganii presented positive correlation with sperm viability. We conclude that, depending on the species of bacteria, bacteriospermia can influence the quality of porcine semen, fresh or stored for 72 hours at 15 oC. B. cepacia and M. morganii improve the quality of diluted fresh semen and of semen stored for 72 hours, respectively. P. putida causes higher damage to fresh semen, while P. mirabilis, P. putida, C. testosterone, E. coli and A. baumannii cause higher damage to stored semen.